The queendom within : rewrite your fairy tale and create your own happily ever after - Hauer, Heidi (Heidi Hauer in pertnership with Whitefox Publishing, 2021)
"Wouldn't it be wonderful to live in a world where all women naturally feel empowered to be who they want to be - where women are free to express themselves and their gifts, and shape the world in a way that is good for all of us? Heidi Hauer has a dream - the dream for every woman to realise that she has choices in her life and that everything she is seeking is already within her power to fulfil. In her inspirational new book, Heidi shows us how to create the life of our dreams, starting from within - our very personal Queendom. We all have moments in life that feel like a crossroads. You may have that sinking feeling that you're in the wrong life - whether you feel trapped in a bad relationship, friendship or in a dead-end job - and secretly you hope for Mr Right to come along and sort everything out. This book will help you find your way back to your truest self, and it will give you the confidence you need to make your own happiness, whether Mr Right is there or not. Through a set of 28 exercises, Heidi Hauer will help you build a strong foundation for your Queendom. The stories and activities are designed to help you identify your hopes and dreams, who you are and where you aspire to be. The results you get will depend on how far you allow yourself to go as you work through the exercises, each of which is designed to be completed in one day. Practical, reassuring and truly inspiring, Heidi's book encourages you to invest your time and energy in yourself. Along the way, your prince may come - or not. But there's a good chance that you'll be able to relax and release your need to control the outcome of your story so your own fairy tale can come true."--